Study of Coal Ash Content Separation in Mallawa Area using The Dense Medium Separation Method - Arifin, Mubdiana; Bakri, Suriyanto; Juradi, Muhammad Idris; Nurhawaisyah, Sitti Ratmi; Zulkarnaen, Dina (Journal of Metallurgical Engineering and Processing Technology, 2025)
Coal remains a major energy source globally, particularly for power generation and industries like iron, steel, chemicals, and cement. Indonesia's coal reserves are widespread, spanning regions such as Aceh, South Sumatra, East Kalimantan, and South Kalimantan. The Mallawa Formation in South Sulawesi also has coal, but it is of low quality due to high ash content, which lowers the calorific value and increases environmental pollution. Therefore, beneficiation is necessary to reduce ash content. The Dense Medium Separation method effectively separates coal from impurity minerals based on density. This study aims to evaluate ash reduction and separation yield across various coal fraction sizes. The coal washing process was conducted on fractions -60+80, -80+100, -100+150, and -150+200 mesh, using a perchloroethylene solution with a density of 1.6 g/ml as the separation medium. Initial coal sample analyses included proximate, calorific value, total sulfur, and mineral matter. Results showed Mallawa coal has 2.94% moisture, 40.60% volatile matter, 47.39% fixed carbon, 9.07% ash, 2.41% total sulfur, and 7053 kcal/kg calorific value, containing quartz, pyrite, calcite, and chlorite minerals. The DMS process on the -150+200 mesh fraction gave the best outcomes, with 50.39% ash elimination and 30.7% yield, making it the optimum size for ash separation in Mallawa coal.